Impact of Quran in treatment of the psychological disorder and spiritual illness - Saged, Ali Ali Gobaili; Mohd Yusoff, Mohd Yakub Zulkifli; Abdul Latif, Faizuri; Hilmi, Syed Mohammad; Al-Rahmi, Waleed Mugahed; Al-Samman, Ahmed; Alias, Norma; Zeki, Akram M. (Springer New York LLC, 2018)
This paper studies the effect of Quranic therapy on psychological diseases and spiritual diseases. The experiments have been conducted on a random sample with 121 patients from both genders. The procedures that have been followed were different sessions with the patients, who were given some verses from the Holy Quran to listen within a specific period of time. After that, each patient was given a remedy program. This study aimed to measure the effectiveness and responsiveness of patients to receive treatment through Quran. This study highlighted the employment of a quantitative research, which achieved its objective through validity and reliability. The results of the effectiveness factor came after ability and willingness and gave a result of 92.6% for those who support the contention that the Quran has a significant healing influence. Also, some of the patients who regularly attended Quranic therapy sessions have been successfully cured, 81.8% of the sample believe that Quranic therapy sessions support their health needs. This study has empirically proved that the sound of the Holy Quran is an effective treatment for those who suffer from spiritual and psychological issues. Folk medicine and other traditional methods of treatment are important field of study that require further investigation. The study also illustrates that it's highly important for patient to have confidence in his doctor or healer. Furthermore, our results show that the ability and willingness positively and significantly are related to the effectiveness and responsiveness, also effectiveness positively and significantly related to the responsiveness. Therefore, the patients satisfied to receive treatment through Quran and they have the ability and willingness to do so as they believe that Quran is an essential part of their life.